Enhance of Flavor and Some Microbial, Physiochemical and Sensory Properties of Yogurt by Threonine and Glycine - Al-Zobaay, Watban J.; Al-Zobaay, Amir H. (Diyala Agricultural Sciences Journal, 2022)
This study was aimed to enhance the flavor and some microbial, physiochemical and sensorial properties of yogurt by threonine and glycine. This study included the estimation (acetaldehyde, acetone and ethanol), acetaldehyde content was 13.46, 13.9, 19.52, 13.99, 28.76, 27.31 and 18.52 mg L-1 for (A) control treatment, (B) glycine 1g /L , (C) threonine 1 g/ L, (D) glycine 3 g/ L, (E) threonine 3 g/ L, (F) threonine 3g + glycine 1g / L and (G) glycine 3g + threonine 1g / L treatments respectively. Acetone content was 8.38, 8.26, 5.71, 8.12, 3.84, 3.11 and 5.49 mg L-1 for A, B, C, D, E, F and G treatments respectively. Ethanol content was 10.25, 10.17, 6.39, 10.16, 4.56, 4.16 and 6.21 mg L-1 for A, B, C, D, E, F and G treatments respectively. Lactobacillus bulgaricus count after the first day of manufacture were 7.38, 7.34, 7.49, 7.39, 7.70, 7.68 and 7.50 cfu mL-1 for A, B, C, D, E, F and G treatments respectively, after 28 days of manufacture was 6.25, 6.23, 6.32, 6.27, 6.51, 6.47 and 6.38 cfu mL-1 for A, B, C, D, E, F and G treatments respectively. Streptococcus thermophilus count after the first day of manufacture were 9.20, 9.14, 9.38, 9.30, 10.62, 10.53 and 9.47 cfu mL-1 for A, B, C, D, E, F and G treatments respectively, after 28 days of manufacture were 8.25, 8.11, 8.34, 8.27, 9.17, 9.11 and 8.36 cfu mL-1 for A, B, C, D, E, F and G treatments respectively after 28 days. The chemical composition did not change, there were no significant differences compared with treatments. Sensory evaluation score showed significant differences (P≤0.05) among the treatments.